An evaluation of patient's decisions regarding dental prosthetic treatment - Nupur D Shrirao; Saee P Deshmukh; Neelam A Pande; Usha M Radke (Wolters Kluwer Medknow Publications, 2016)
Introduction: For fabricating dental prostheses that meet patients' demands and have good longevity and function, appropriate treatment planning and decision-making are required. Therefore, not only technical skills and clinical judgment of the dentist are needed, but also patients' attitude toward treatment plays a critical role in posttreatment satisfaction. Aim: The aim of this study is to investigate the factors affecting decision-making and the selection of dental prosthesis by the patients. Materials and Methods: A cross-sectional survey to determine patients' attitudes about replacement of teeth was conducted. This survey was performed with the help of a prevalidated questionnaire, which contained the demographic data of every patient, whether or not they accept the treatment plan proposed by the dentist, and a close-ended multiple choice question stating the reasons cited by them if they decline the proposed treatment plan. Results: The data were subjected to statistical analysis by Chi-square test at a significance level of P< 0.05. A relationship between the demographical information such as age, gender, educational status, marital status, and monthly income of each patient and the single best reason opted by them to not undergo the proposed treatment plan was established. Conclusions: In the sample of population studied, most of the patients declined the proposed treatment plan and accepted the alternate one. High expenditure is the most common reason for this rejection.